Personalized Learning as A Method of Moral and Intellectual Development in The Humanitarization of the Post-Industrial Society - Kondratiev, Sergey Vladimirovich (2020)
The article presents the post-industrial society problem in the context of personal self-existence of the individual. A spiritually oriented humanitarian paradigm in the intellectual and moral development of the individual in the framework of solving the post-industrial society problems is identified. Personalized learning is considered as a special learning type focused on the personal and intellectual development of the individual on the way from egocentrism to altruism. Intellectual development in the framework of metacognitive learning strategies is presented. The spiritual and moral development of students is defined as personal reflection development. The article presents the empirical study data on the moral orientation of students' personality in educational organizations.